New Concepts in Oxidation Processes - Genty, Eric (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of Catalysts aims to cover the recent progress and novel trends in the field of catalytic oxidation reaction. Topics addressed in this special issue concern the influence of different parameters on catalytic activity at various scales (atomic, laboratory, pilot, or industrial scales), the development of new catalytic materials of environmental or industrial importance, as well as the development of new methods, both microscopic and spectroscopic, to analyze oxidation processes.